2019
DOI: 10.1007/s10974-019-09532-y
|View full text |Cite
|
Sign up to set email alerts
|

Thin filament dysfunctions caused by mutations in tropomyosin Tpm3.12 and Tpm1.1

Abstract: Tropomyosin is the major regulator of the thin filament. In striated muscle its function is to bind troponin complex and control the access of myosin heads to actin in a Ca 2+-dependent manner. It also participates in the maintenance of thin filament length by regulation of tropomodulin and leiomodin, the pointed end-binding proteins. Because the size of the overlap between actin and myosin filaments affects the number of myosin heads which interact with actin, the filament length is one of the determinants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 124 publications
1
24
0
1
Order By: Relevance
“…Tpm3.12 carries an extra Met at the N-terminus and Asp2 to Glu3 substitution [ 8 ]. These few changes can be responsible for stronger interactions between tropomyosin with actin and between adjacent tropomyosin molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tpm3.12 carries an extra Met at the N-terminus and Asp2 to Glu3 substitution [ 8 ]. These few changes can be responsible for stronger interactions between tropomyosin with actin and between adjacent tropomyosin molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous myopathy-related mutations were found in TPM1 and TPM3 genes, which encode Tpm1.1 and Tpm3.12 isoforms, respectively, however none of the mutations found in Tpm3.12 were identified in Tpm1.1 [ 8 ]. The fact that single substitutions in TPM3 may cause very severe forms of skeletal myopathy characterized by muscle weakness, hypotrophy of type 1 fibers and disproportion in the number of type 1 and type 2 fibers [ 9 , 10 , 11 , 12 ], provides additional evidence for the importance of the fiber type-specific tropomyosin isoforms in the function of skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The structural and functional effects of a number of Tpm mutations associated with different variants of congenital myopathy have been investigated previously [ 29 , 31 , 32 ]. It was found that the Tpm mutations can change several features of Tpm and affect different aspects of muscle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Numerous point mutations have been discovered in the TPM3 gene, associated with generalized muscle weakness and linked to the genesis of such diseases of slow skeletal muscles as nemaline myopathy, congenital fiber-type disproportion (CFTD), and cap disease. [13][14][15][16][17] Clinical manifestation, histology, and genetics of myopathies caused by these mutations have been described. [13][14][15][16] At this, the properties of myopathy associated mutations of Tpm are poorly understood.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] Clinical manifestation, histology, and genetics of myopathies caused by these mutations have been described. [13][14][15][16] At this, the properties of myopathy associated mutations of Tpm are poorly understood. It was shown that the M9R mutation induces nemaline myopathy.…”
mentioning
confidence: 99%